DUNIA SASTRA FRANCOPHONE DI ARAB-MAGREB - Siti Hariti Sastriyani (Humaniora, 2006)
Former countries under French colonialism have been forced to adopt French as their second language. Among others, are in Arabian countries called Maghrebes. The adoption of French language beyond France has impacts on literature activities as a tradition. Genres created express nationalism depicting struggles against colonialism, independences, and freedoms. They have evidenced cultural contacts among Maghrebes and French. The Arabian-Maghribian genres are written by authors from Algier, Morroco, and Tunesse. They involve poems, novels and plays. Literature works that Arabian authors write involve epics, autobigraphies, family novels, detective novels, and historical novels, also documentaries.